Kinematic sequence patterns according to movement time of Choku-tsuki in Karate Kumite - Kim, T.-W.; Kim, J.-N. (Korean Journal of Sport Biomechanics, 2020)
Objective: The purpose of this study was to investigate the kinematic sequence patterns according to movement times during Karate choku-tsuki. Method: Ten Korea national Karate athletes participated in this study. Participants asked to perform jodan and chudan choku-tsuki. 30 infrared cameras were used to measure angular kinematic of elbow, shoulder, trunk, pelvis, hip, knee, ankle. Results: The two-way repeated measures ANOVA revealed significant effects for the joints (p<.05). But no significant effect for the movement time and interaction of joints x movement time existed for the kinematic sequence variables. Conclusion: For karate kumite players to reduce the movement time of punch, it is necessary to train kinematic sequences that allow each joint to rotate at a relatively similar timing.